National approaches to ensuring responsible animal treatment through state mechanisms - Mukasheva, A.A.; Narzullaev, O.Х.; Nurekeshov, T.K. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
Kazakhstan's official system for guaranteeing the humane treatment of animals is examined in this article. The Law of the Republic of Kazakhstan "On Responsible Treatment of Animals," enacted on December 30, 2021 (hereinafter – “LRTA”), which established the framework for the establishment of a new legal institution, is examined in particular. The authors consider the theoretical and legal nature of the concepts of “state regulation” and “public administration,” disclosing their specificity and delimitation in relation to the sphere of animal protection. The study organizes the mechanism's primary functions, including information gathering and analysis, cadastre and state record maintenance, strategic direction development, lawmaking, resource allocation, control and supervision, and educational activities. It is noted that the effectiveness of legal regulation largely depends on the coordinated interaction of state bodies and the completeness of legislative consolidation of functions. The necessity of supplementing the law with provisions on state control and civic education is substantiated, since only a comprehensive approach that combines administrative and educational measures can ensure the sustainable formation of a culture of humane treatment of animals. The authors conclude that further development of legislation in this field is a necessary condition for strengthening the system of environmental law and implementing the principles of humanism in modern society.